Liberators in times of revolution. The participation of women in the Independence of Peru and Latin America - Morán Ramos, Daniel (2021)
After the arrival of the bicentennial to the different countries of Latin America, our research aims to highlight the participation of women in the independence of their respective nations, in order to commemorate these dates and highlight their role as a historical subject. In this way, it will be taken as a starting point what is expressed by recent historiography about the actions of the heroines of independence, both in their work as spies for the patriot army or risking their lives on the battlefield. Thus, this essay will be carried out with a gender perspective, focusing on important figures such as Manuela Sáenz, María Parado de Bellido, Policarpa Salavarrieta, Francisca Zubiaga, Rosa Campusano; Furthermore, the actions of different groups of women will be pointed out, whose names we do not know; however, their actions were relevant for the independence of Peru and Latin America.